Homonymous visual field defect and retinal thinning after occipital stroke - Avan Sabir Rashid; Darian Rashid; Ge Yang; Hans Link; Helena Gauffin; Yumin Huang‐Link (Brain and Behavior, 2021)
Abstract Introduction Stroke is the most common cause of homonymous visual field defects (VFD). About half of the stroke patients recover from VFD. However, relationship between VFD and retinal changes remains elusive. Purpose To investigate the association between occurrence of VFD, changes of macular ganglion cell and inner plexiform layer (GCIPL) and its axon retinal nerve fiber layer (RNFL) detected with optical coherence tomography (OCT). Patients and methods The study consists of retrospective review of medical records and follow‐up examinations. Patients with acute occipital stroke were registered. VFD was identified with confrontation and/or perimetry tests at the onset. At follow‐up, the patients were examined with visual field tests and OCT measurements. Results Thirty‐six patients met the inclusion criteria. At onset, 26 patients (72%) had VFD. At follow‐up >1 year after stroke, 13 patients (36%) had remaining VFD: 5 had homonymous hemianopia, 5 had homonymous quadrantanopia, and 3 had homonymous scotomas. Average thickness of GCIPL and RNFL were significantly reduced in each eye in patients with VFD compared to non‐VFD (NVFD) (p < .01 for all comparisons). Thickness of superior and inferior RNFL quadrants was significantly reduced in VFD compared to NVFD (p < .01 for both). Among these 13 patients, 4 had characteristic homonymous quadrant‐GCIPL thinning, 2 had characteristic homonymous hemi‐GCIPL thinning, and 7 had diffuse GCIPL thinning. Conclusion GCIPL and RNFL thinning were observed in the patients with VFD. GCIPL thinning appears in two forms: atypical diffuse thinning, or homonymous hemi‐GCIPL thinning. Examining GCIPL and RNFL provides easy and reliable objective measures and is therefore proposed to be of predictive value on visual function.